2013
DOI: 10.1167/iovs.12-11320
|View full text |Cite
|
Sign up to set email alerts
|

The ROCK Inhibitor Eye Drop Accelerates Corneal Endothelium Wound Healing

Abstract: Citation: Okumura N, Koizumi N, Kay EP, et al. The ROCK inhibitor eye drop accelerates corneal endothelium wound healing. Invest Ophthalmol Vis Sci. 2013;54:243954: -250254: . DOI:10. 1167 PURPOSE. To evaluate the effect of Rho kinase (ROCK)-inhibitor eye drops on a corneal endothelial dysfunction primate model and human clinical case series of corneal endothelial dysfunction.METHODS. As a corneal-endothelial partially injured model, the corneal endothelium of seven cynomolgus monkeys was damaged by transcorn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(192 citation statements)
references
References 31 publications
5
181
1
5
Order By: Relevance
“…A phase 1 clinical trial was performed in Japan involving 10 healthy volunteers. This study confirmed that Y27632, applied as 10 mM eye drops 6 times daily for 7 days, did not cause any systemic or local side effects [30]. Eight patients who suffered from corneal deficiency were subsequently enrolled to test the feasibility of the drug in pathological conditions.…”
Section: Corneal Wound Healingsupporting
confidence: 65%
See 1 more Smart Citation
“…A phase 1 clinical trial was performed in Japan involving 10 healthy volunteers. This study confirmed that Y27632, applied as 10 mM eye drops 6 times daily for 7 days, did not cause any systemic or local side effects [30]. Eight patients who suffered from corneal deficiency were subsequently enrolled to test the feasibility of the drug in pathological conditions.…”
Section: Corneal Wound Healingsupporting
confidence: 65%
“…After two days the difference between the treated and the non-treated eye in the size of the wound was remarkable. Furthermore, after one week non-contact specular microscopy showed normal cell morphology and cell density (of 3000 cell/mm 2 ) in the treated group, in contrast with the control group, where the examined area exhibited enlarged corneal endothelial cells (CEC) and a cell density of only 1500 cells/mm 2 [30].…”
Section: Corneal Wound Healingmentioning
confidence: 80%
“…In vivo human corneal endothelial cells are thought to be arrested at the G1 phase of the cell cycle; thus, proliferation is inhibited 26. A purely medical treatment for corneal endothelial disease has been sought for quite some time, and several interesting agents have been explored for this purpose, such as EDTA,27 EGF, PDGE, FGF‐2,28 siRNA of Connexin 43,29 R‐spondin 130 and ROCK inhibitor 31. However, these agents have not yet been introduced into the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…3. Facilitate corneal endothelium wound healing: RKI Y-27632 has been shown to increase corneal endothelial cell density and restore function in animals with partially injured cornea 23 , suggesting a role for rhokinase inhibitors as a potential therapeutic treatment for certain forms of corneal endothelial cell dysfunction in humans.…”
Section: Improve Blood Flow To the Optic Nervementioning
confidence: 99%